2012
DOI: 10.1097/wnp.0b013e318257ca9d
|View full text |Cite
|
Sign up to set email alerts
|

Approximate Entropy Analysis of Event-Related Potentials in Patients With Early Vascular Dementia

Abstract: This study investigated differences in event-related potential (ERP) parameters among early vascular dementia (VD) patients, healthy elder controls (ECs), and young controls (YCs). A visual "oddball" color identification task was performed while individuals' electroencephalograms (EEGs) were recorded. Approximate entropy (ApEn), a nonlinear measure, along with P300 latencies and amplitudes were used to analyze ERP data and compare these three groups. The patients with VD showed more complex ERP waveforms and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 32 publications
1
14
0
Order By: Relevance
“…It has been shown that the detection of target stimuli would elicit an event-related potential (ERP) component, P300, in a typical oddball paradigm [23]. Prolonged response time indicates a delay in the detection of target stimuli and an increased P300 latency in VaD patients [24,25]. This study further confirmed the decline of the brain functions in VaD patients.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…It has been shown that the detection of target stimuli would elicit an event-related potential (ERP) component, P300, in a typical oddball paradigm [23]. Prolonged response time indicates a delay in the detection of target stimuli and an increased P300 latency in VaD patients [24,25]. This study further confirmed the decline of the brain functions in VaD patients.…”
Section: Discussionsupporting
confidence: 60%
“…Based on such consideration, the DTF connectivity were integrated into 5 frequency bands, i.e. ı (0.5-3.5 Hz), Â (4-7 Hz), ˛1 (8-10 Hz), ˛2 (11)(12)(13) and (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), and then statistic tests were performed again. Significant directional connectivity was visualized over the scalp surface using the eConnectome software package [22].…”
Section: Resultsmentioning
confidence: 99%
“…The results suggest that visual cognitive function is selectively impaired in PDD and DLB, and this, at an early stage of visual processing. In VD, the latency of P3 is delayed and its amplitude decreased, suggesting that these individuals may have fewer attention resources to devote to processing stimuli …”
Section: Visual Dysfunction In Dementiamentioning
confidence: 99%
“…In VD, the latency of P3 is delayed and its amplitude decreased, suggesting that these individuals may have fewer attention resources to devote to processing stimuli. 138 …”
Section: Visual Evoked Potentialsmentioning
confidence: 99%
See 1 more Smart Citation